Adolescents’ Attitude towards Masturbation: Practical Study on a Sample of Senior High School Students in the Cape Coast Metropolis of Ghana - Priscilla Commey Mintah; Kwaku Darko Amponsah; Grace Sintim Adasi; Rosina Okyere Amponsah (European Scientific Journal, ESJ, 2020)
There are societal variations as to how masturbation is regarded because some societies regard it as a religious or cultural bizarre, while others tolerate it on biological grounds. This study employed a descriptive survey design to explore adolescents' attitudes towards masturbation in selected senior high schools in the Cape Coast Metropolis of Ghana. The target population was formed by form two students in both schools. The total population for the second-year students in the boys' school was 509, while the second-year students in the girls' school were 496. Specifically, it was carried out in two single-sex Senior High Schools (SHS) in the Cape Coast Metropolis. Purposive sampling was employed to select single-sex schools in the metropolis, as they are noted for the practice of masturbation. Three hypotheses on masturbatory practices, attitudes toward masturbation and masturbatory practices and self-concept were formulated for the study. The results indicated that implicitly, both sexes’ masturbatory practices are similar. Both sexes also have similar attitude towards masturbation; as well as the masturbatory practices and self-concept in the Cape Coast Metropolis. Similarly, it was found that the attitude of both sexes towards masturbation was characterised by ambivalence, as they regarded it to be an irreligious and bad practice, yet, they covertly practised it. It was recommended that stakeholders should give adolescents thorough sexual education without expressing their prejudices concerning masturbation. They should be made to understand that sexual urges are a natural part of their development that must, however, be controlled for moral and spiritual reasons.